2009
DOI: 10.1017/s1138741600001827
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Reading Strategies in School-Age Children

Abstract: Learning to read is one of the most important cognitive milestones in the human social environment. One of the most accepted models explaining such process is the Double-Route Cascaded Model. It suggests the existence of two reading strategies: lexical and sublexical. In the Spanish language there are some contradictions about how these strategies are applied for reading. In addition, there are only a few studies dealing with the analysis of shifts between them, achieving a fluent reading process. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
3
0
1
Order By: Relevance
“…Previous research suggests that flexibility increases across childhood, especially during the elementary years, and evinces wide individual variation regardless of age (Bock, Gallaway, & Hund, ; Cartwright, ; Cartwright, Marshall, Dandy, & Isaac, ; Huizinga & van der Molen, ). These gains have been found for both general flexibility—domain‐general aspects of shifting commonly included as one aspect of executive functioning (Bock et al, ; Cantin, Gnaedinger, Gallaway, Hesson‐McInnis, & Hund, )—and reading‐specific flexibility—domain‐specific aspects of coordination relevant for reading (Cartwright et al, ; Diaz et al, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research suggests that flexibility increases across childhood, especially during the elementary years, and evinces wide individual variation regardless of age (Bock, Gallaway, & Hund, ; Cartwright, ; Cartwright, Marshall, Dandy, & Isaac, ; Huizinga & van der Molen, ). These gains have been found for both general flexibility—domain‐general aspects of shifting commonly included as one aspect of executive functioning (Bock et al, ; Cantin, Gnaedinger, Gallaway, Hesson‐McInnis, & Hund, )—and reading‐specific flexibility—domain‐specific aspects of coordination relevant for reading (Cartwright et al, ; Diaz et al, ).…”
mentioning
confidence: 99%
“…We know that reading-specific flexibility is related to reading comprehension, as evidenced by research with early readers (Cartwright, 2002;Cartwright et al, 2010;Colé, Duncan, & Blaye, 2014;Diaz et al, 2009) and college students (Cartwright, 2007;Cartwright et al, 2006). Importantly, Cartwright (2002) found that reading-specific flexibility contributed to reading comprehension, even after controlling for age, domain-general flexibility, decoding skill, and verbal ability.…”
mentioning
confidence: 99%
“…En cambio, si bien los tiempos de reacción de las palabras aumentan a medida que los estímulos presentan mayor cantidad de sílabas, dicho aumento es menor que el observado en las no-palabras. Esta diferencia observada según el tipo de estímulo puede explicarse por la utilización de la ruta léxica: estudios longitudinales demuestran que las estrategias de lectura en español cambian a través del proceso de aprendizaje lector (Acha y Perea, 2008;Cuetos y Suárez Coalla, 2009;Jiménez y Guzmán, 2003;Sanabria Díaz et al, 2009). Durante las etapas iniciales, los lectores acuden a una lectura que se apoya, fundamentalmente, en la ruta sublexical, tanto para las palabras como para las no-palabras.…”
Section: Discussionunclassified
“…Synthetic Phonics method was made popular by Diaz (2009). This is a method to teach phonics to children when learning to read.…”
Section: Different Phonics Approachesmentioning
confidence: 99%